Implementasi Kurikulum Merdeka dalam Pembelajaran PPKN : Studi Literatur - Hikmah Mulia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This article reviews the implementation of the Independent Curriculum in the learning process of Pancasila and Citizenship Education (PPKn) subjects using literature analysis. The Independent Curriculum is an innovative step that aims to improve the quality of learning by providing flexibility for teachers and students. Its implementation in PPKn has been applied in several schools such as SMA Negeri 1 Pringgabaya and MA Negeri 1 Ngawi. The findings show that the Independent Curriculum in PPKn is implemented using open modules, formative and summative assessments, and project-based, collaborative, and problem-based learning methods. The use of the Independent Curriculum allows students to express themselves, learn independently, and develop their talents and abilities. This article states that the implementation of the Independent Curriculum in PPKn has the potential to improve the quality of meaningful learning and in accordance with the needs of students.